2012 IEEE 62nd Electronic Components and Technology Conference 2012
DOI: 10.1109/ectc.2012.6249083
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of electrical properties of nanomagnetic materials through meander-shaped inductor and inverted-F antenna structures

Abstract: This paper presents processing, integration and characterization of a new class of magneto-dielectrics consisting of metal nanoparticles in a polymer matrix for antenna applications. These nanomagnetic materials exhibit several attractive features for antenna applications, such as simpler thick-film processing, higher permittivity and permeability, and lower loss. Extraction of permeability and loss for such materials is usually cumbersome because both the permittivity and permeability are unknown. The meander… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Thus, an optimized value of dielectric and loss tangent was obtained. As a comparison, Han et al [30] had reported a meander-shaped inductor component for nanocomposite material characterization. The material properties extraction method and fabrication technique, described in [30], which have the benefits of material usage minimization and uncomplicated fabrication, are similar in this paper.…”
Section: Measurement and Characterization Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an optimized value of dielectric and loss tangent was obtained. As a comparison, Han et al [30] had reported a meander-shaped inductor component for nanocomposite material characterization. The material properties extraction method and fabrication technique, described in [30], which have the benefits of material usage minimization and uncomplicated fabrication, are similar in this paper.…”
Section: Measurement and Characterization Ofmentioning
confidence: 99%
“…As a comparison, Han et al [30] had reported a meander-shaped inductor component for nanocomposite material characterization. The material properties extraction method and fabrication technique, described in [30], which have the benefits of material usage minimization and uncomplicated fabrication, are similar in this paper. Since the electrical properties of capacitor component depend on the physical dimension of the component and its material properties, essentially, the capacitance and Q-factor of the passive component with and without the ink were also measured.…”
Section: Measurement and Characterization Ofmentioning
confidence: 99%
“…However, two different resonant sensors [27,28] are required to sense permittivity and permeability independently. This makes the system complicated and increases its cost and size.…”
Section: Introductionmentioning
confidence: 99%